Upaya Meningkatkan Keaktifan dan Minat Belajar IPAS (Sosial) Peserta Didik Menggunakan Media “ASEAN GO” di Sekolah Dasar Negeri 060875 Medan - Lubis, Nur Halimah; Pratiwi, Indah; Kartika, Nur (Medan Resource Center, 2025)
This study investigates the effectiveness of using educational game media based on the Monopoly format to enhance student engagement in Social Studies. The research was conducted with fourteen sixth-grade students from an elementary school in North Sumatra. Employing a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, the study followed four key phases: planning, action, observation, and reflection. Data were collected through student engagement questionnaires administered before and after the implementation. Findings demonstrated a significant increase in the average engagement score from 1.87 to 2.99. Additionally, the post-intervention data revealed that the majority of students transitioned into the